KADAR b-hCG PENDERITA MOLA HIDATIDOSA SEBELUM DAN SESUDAH KURETASE - S Aprianti; Syafii Syafii; Hardjoeno Hardjoeno (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Hydatiform mole is an important disease, with a high incidence, many risk factors, and equity spreading. To know and compareb-hCG levels among patients with hydatiform mole before and after curretage was investigated. A retrospective study from January2002 to December 2005 at Dr. Wahidin Sudirohusodo Public Hospital was performed comprising b-hCG levels of hydatiform molepatients before and after curettage. b-hCG level (Elisa’s method) were grouped by age of pregnancy. Among 72 patients, 43 patients withhydatiform mole were found. At trimester I among 10 patients (23.3%), b-hCG level was higher 3 (7.0%), normally 4 (9.3%) and lower3 (7.0%). At trimester II, among 33 patients (76.7%), b-hCG level was higher 12 (27.9%), normal 13 (30.2%) and lower 3 (7.0%).After curretage, b-hCG level was decreased in 35 (81.4%), and increased in 7 (16.3%). Diagnosis of hydatiform mole was establishedin 36 (83.7%) and Gestational Trophoblastic Tumours (GTT) 7 (16.3%). Patients with hydatiform mole had the highest incidence intrimester II with normal b-hCG level and b-hCG level decreased after curretage.